Teachers and Their Functions in Implementing Learning and Creating Through Collaboration Teaching Styles to Improve the Quality of Education - Firmansyah, Bagas; Amalia, Siti; Susanti, Susanti (CV. Rayyan Dwi Bharata, 2024)
The purpose of this research is to find out whether teachers as professional educators have functions and roles in implementing more varied learning styles in order to improve the quality of education, and this research was conducted using descriptive qualitative research methods, and data analysis was used by searching for other article titles. relevant so that this research provides significant results that teachers play a full role in their involvement in improving the quality of learning in order to achieve national education goals. So the overall conclusion of this research is that the presence of teachers has a very important service in teaching and makes every effort to always be able to find solutions in teaching, such as being aware of technological developments so that learning can utilize media, and the application of more modern learning models and strategies.